The Effect Of Financial Planning, Spending Habits, And Sources Of Income On Personal Financial Stability Through Self-Control As A Mediating Variable Among Students In The Faculty Of Economics And Business At The State University Of Makassar - Lilis Sampa; Syamsu Rijal; Hikmayani Subur; Marhawati Najib; Nurjannah (Citakonsultindo, 2026)
This study aims to examine the impact of financial planning, spending habits, and sources of income on personal financial stability through self-control as a mediating variable among students at the Faculty of Economics and Business, Makassar State University. This study employed a quantitative method and surveyed 361 participants; Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data. The results show that financial planning, spending habits, and income sources have a positive and significant effect on personal financial stability as well as on self-control. In addition, self-control was also found to have a positive and significant effect on personal financial stability. Furthermore, this study found that self-control acts as a significant mediating variable in the relationship between financial planning, spending habits, and income sources on personal financial stability.